1983
DOI: 10.1002/ar.1092060107
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic innervation of the penis in control and streptozotocin‐diabetic rats: Evidence of autonomic neuropathy

Abstract: The noradrenergic sympathetic innervation of the penis of control and 4-month streptozotocin-diabetic rats was examined with the glyoxylic acid histofluorescence method. Noradrenergic varicosities were found in the corpora cavernosa in a dense subtunical plexus and in the perisinusoidal and trabecular regions of the erectile tissue, in the corpus spongiosum in perisinusoidal tissue, around large arteries and veins, and around small tortuous arterioles and small draining veins of the corpora cavernosa and spong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 54 publications
0
9
1
1
Order By: Relevance
“…9 The vasoconstrictor neurotransmitter NA is also known to increase in concentration in a variety of tissues including the rat heart, tail artery and whole penis, [10][11][12] and the time course of these changes often involves a peak in concentration that can occur after several, or many months of hyperglycaemia. However, while some authors have found a reduction in the noradrenergic [13][14][15] and nitrergic 16,17 innervation in diabetic erectile tissue, the results on the noradrenergic nerves are not confirmed in a recent publication 12 and in the present work. Changes in the concentration of NA in the CC may or may not influence erectile function, depending on when and where there is an increased release, and indeed if there is a change in release at all, one might expect the inhibition of erection 18,19 and facilitation of detumescence.…”
Section: Introductioncontrasting
confidence: 99%
See 3 more Smart Citations
“…9 The vasoconstrictor neurotransmitter NA is also known to increase in concentration in a variety of tissues including the rat heart, tail artery and whole penis, [10][11][12] and the time course of these changes often involves a peak in concentration that can occur after several, or many months of hyperglycaemia. However, while some authors have found a reduction in the noradrenergic [13][14][15] and nitrergic 16,17 innervation in diabetic erectile tissue, the results on the noradrenergic nerves are not confirmed in a recent publication 12 and in the present work. Changes in the concentration of NA in the CC may or may not influence erectile function, depending on when and where there is an increased release, and indeed if there is a change in release at all, one might expect the inhibition of erection 18,19 and facilitation of detumescence.…”
Section: Introductioncontrasting
confidence: 99%
“…The same group, however, in a different paper illustrating some of the variability of the responses, described either no change or an increase in varicosities at 4 month and 1 month, respectively. 14 Reasons for the discrepancy may be (a) the methodology, (b) Sprague-Dawley rats were used by Felten et al, 13 whereas Wistar rats were used in the present study; (c) Felten et al 14 used a larger dose of STZ at a younger age, and had evidence that there were differences in the response of the sympathetic nerves if diabetes was induced at a later age. Felten et al 13,14 also used rats which had a greater blood glucose level and excluded animals with a blood glucose of less than 300 mg/dl, and finally (d) they included the sub-tunical plexus where the sympathetic terminals are very densely packed.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…From these studies the existence of a localized (i.e. found in some organs and not in others) impairment of adrenergic, serotoninergic and peptidergic innervation was demonstrated in streptozotocin-treated animals (5,8,10,11,16) . On the contrary, information concerning the innervation pattern of blood vessels in diabetes is almost exclusively limited to studies of vascular reactivity after infusion or in vitro application of catecholamines (5).…”
Section: Discussionmentioning
confidence: 96%